Effector discovery and characterisation in the Fusarium graminearum-wheat floral interaction - Walker, Catherine Holly (2020)
Fusarium graminearum is the causal agent of Fusarium Head Blight (FHB) – a highly hazardous wheat disease which results in crop losses and mycotoxin contamination. A recent transcriptomic investigation of the F. graminearum-wheat interaction revealed an up-regulation in hundreds of genes encoding small secreted proteins (SSPs), or putative effectors, during infection which we hypothesise contribute towards pathogenicity. The aim of this study was therefore to bioinformatically identify and then functionally characterise effector candidates in wheat and Nicotiana benthamiana using a range of post-genomics techniques.